PENERAPAN HEUTAGOGY LEARNING DALAM PROGRAM MBKM DI PTKIS - Sutisna; R. Suyato Kusumaryono; Juwita Ramadani Fitria; Anjani Putri Belawati Pandiangan; Norsyam Amaly (al-Afkar, Journal For Islamic Studies, 2022)
THE IMPLEMENTATION OF HEUTAGOGY LEARNING IN THE MBKM PROGRAM IN PTKIS The study's goal is to learn about the main points of MBKM policies, learning activities "three semesters of student learning rights," and steps for implementing heutagogy learning in the MBKM program "three semesters of learning rights outside study programs" at PTKIS. This research is important and interesting to conduct as a supplement to similar research that is still providing minimal and constructive input to PTKIS that have not/are not implementing MBKM. This research method is qualitative, and it is based on library research. The data gathered from various books, journals, and previous research findings were analyzed using the Miles and Hubarman paradigm, which includes data collection, data reduction, data presentation, and verification. The study's findings are as follows: (1) there are four main points of MBKM policies that all PT/PTKIS must implement; (2) there are eight MBKM activities "right to learn three semesters outside the study program" that all PT/PTKIS must hold; and (3) there are eight steps of heutagogy learning from Blaschke Lisa Marie that are suitable to be applied in the MBKM program "right to learn three semesters outside the study program" as the final level and continuum of pedagogy and andragogy learning.